2012
DOI: 10.1097/00001756-201207110-00011
|View full text |Cite
|
Sign up to set email alerts
|

Math5 (Atoh7) gene dosage limits retinal ganglion cell genesis

Abstract: The basic helix-loop-helix factor Math5 (Atoh7) is critical for the determination of retinal ganglion cell (RGC) fate in mice. Recently, genome-wide association studies have identified the ATOH7 locus as a major determinant of variation in the human optic disc area, which is directly correlated with the RGC number. These studies suggest that the level of Math5 expression may determine the ultimate number of RGCs. To test this hypothesis, we systematically compared optic nerve area and RGC axon number in C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our WT C57BL/6 data match those obtained via other automated counting approaches (59,60). Consistent with previous analyses (19), there was no significant difference in the number or density of RGCs in adult Atoh7 KO/+ and SE/+ retinas compared to WT, and KO/KO retinas had scant RGCs. However, both SE/KO and SE/SE retinas had significantly fewer RGCs.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our WT C57BL/6 data match those obtained via other automated counting approaches (59,60). Consistent with previous analyses (19), there was no significant difference in the number or density of RGCs in adult Atoh7 KO/+ and SE/+ retinas compared to WT, and KO/KO retinas had scant RGCs. However, both SE/KO and SE/SE retinas had significantly fewer RGCs.…”
Section: Resultssupporting
confidence: 90%
“…Postnatal Atoh7 SE Mutants Have Fewer RGCs. In a previous study, we showed that a 50% reduction in Atoh7 dosage impairs RGC genesis but does not alter the final number of RGCs, by comparing optic nerve axons in neonatal and adult Atoh7 +/+ and KO/+ mice (19). The developing nervous system thus compensates for defective RGC genesis by decreasing the extent of neonatal RGC culling (55,56), a normal process that matches the number of RGCs to postsynaptic targets in the brain.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations